Chemoselective catalytic hydrodefluorination of trifluoromethylalkenes towards mono-/gem-di-fluoroalkenes under metal-free conditions - Jingjing Zhang (Nature Portfolio, 2021)
Fluorine-containing moieties show significant effects in improving the properties of functional molecules. Here the authors show diazaphospholene-catalyzed hydrodefluorination of trifluoromethylalkenes to chemoselectively construct gem-difluoroalkenes and terminal monofluoroalkenes by simple adjustment of the reactant stoichiometry.